Entorno familiar y el desarrollo comportamental en los adolescentes de la Unidad Educativa Nicolás Infante Díaz - Choez Macias, Thalia Alejandra (2019)
Modern adolescents are traversed by numerous events that involve knowing how to confront, solve and solve in the best way the difficulties or conditions that are shown and that can form stress. Tenth grade students of basic education are protagonists in their family environments, in situations such as victimizer or victim of physical and psychological aggression, spousal dissolution, loss of a family member, the same ones that are reflected in the current problem in their behavioral development. it is reflected inside and outside the classroom. In the present investigation the student's family environment was related to the aggressive behavioral developments and that have been transcended more frequently in the parallels of the last years of basic education, since there is a great increase of violence in our society, which is has been reproducing in both fiscal and private educational institutions. In the investigation, the problem was determined through the structuring of the theoretical framework, to properly establish the variables. The model that guided the research is the training and it was concluded to conduct a qualitative and quantitative research, giving importance to the description of the cause-effect relationship. Regarding the methodology, the research is qualitative-quantitative since there are multiple social realities in which the human being participates as an active entity of transformation, by the objectives, it is applied; for the place it is of field, since it will be developed in the place of the facts, it is documentary bibliography.